Occurrence of hyphomycetes and actinomycetes in red-yellow latosol from a cerrado region in Brazil - Raymundo Jr., Olavo [UNESP]; Tauk-Tornisielo, Sâmia Maria [UNESP] (My University, 1997)
A study to quantify the populations of filamentous fungi and actinomycetes was undertaken in a cerrado area, in Corumbataí county, Sã Paulo, at different depths of medium-textured red-yellow latosol, correlating them to humidity, organic matter, pH of the soil and climatic factors. The technique used was fee serial dilution of composite soil samples (n=4), using Martin's medium with streptomycin for filamentous fungi and a starch medium for actinomycetes. The number of filamentous fungi was more abundant was higher between 5 cm and 50 cm depth. There were two-monthly variations in the number of filamentous fungi and actinomycetes. A sharp drop in fungi Was foundi in May 1988 at all depths of the soil, when there was lower air temperature and an atypically high monthly rainfall fer this period in the cerrado. Statistically significant and directly proportional correlatioas were obtained between the number of actinomycetes and the rainfall at depths of 0 to 5 cm and 50 to 100 cm. The results obtained in the different soil concentration of microorganisnis, mainly the filamentous fungi, together with the highest organic matter content.
Keywords: Actinomycetes; Cerrado; Filamentous fungi; Soil